2006
DOI: 10.1016/j.physletb.2006.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Z6 symmetry, electroweak transition, and magnetic monopoles at high temperature

Abstract: Z 6 symmetry, electroweak transition, and magnetic monopoles at high temperature AbstractWe consider the lattice realization of the Standard Model with an additional Z 6 symmetry. Numerical simulations were performed on the asymmetric lattice, which corresponds to the finite temperature theory. Our choice of parameters corresponds to large Higgs masses (M H > 90 Gev). The phase diagram was investigated and has been found to be different from that of the usual lattice realization of the Standard Model. It has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Namely, we consider their percolation properties that are related to their possible condensation. In the finite temperature theory it was found that the electroweak transition is accompanied with the condensation of the Nambu monopoles and the condensation of the Z-strings [27][28][29]. Here we find that in the zero-temperature model this occurs as well.…”
Section: Introductionsupporting
confidence: 65%
“…Namely, we consider their percolation properties that are related to their possible condensation. In the finite temperature theory it was found that the electroweak transition is accompanied with the condensation of the Nambu monopoles and the condensation of the Z-strings [27][28][29]. Here we find that in the zero-temperature model this occurs as well.…”
Section: Introductionsupporting
confidence: 65%
“…For a definition of those notations see, for example, [34].) Therefore, Σ can be treated as the worldsheet of a quantum Z-string [31,7,30]. ‡ On the classical level the monopole -like topological objects with nontrivial hypercharge flux have an infinite self energy.…”
Section: Nambu Monopolesmentioning
confidence: 99%
“…In our earlier papers we considered the appearance of an additional discrete symmetry in the fermion sector of the standard model [4][5][6][7]. This additional symmetry allows us to define the standard model with the gauge group SU (3) × SU (2) × U(1)/Z, where Z is equal to Z 6 , or to one of its subgroups: Z 3 or Z 2 .…”
Section: Referencementioning
confidence: 99%
See 2 more Smart Citations